Self-Regulated Learning in the Teaching of Speaking and Listening Skills Integrated with Self-Confidence and Linguistic Awareness: A Lesson Learned from a University in Turkey - Suratullah, Gauzen; Ahmad, Sameena Banu; Hassan, Ahmad Javed; Manu, Said Malika Tridane (Journal of Language and Literature Studies, 2023)
The amalgamation of self-regulated learning, self-confidence, and linguistic awareness within the teaching of speaking and listening skills at Islamic-affiliated schools holds tremendous promise in empowering learners to become independent, proficient, and self-aware language users. By encouraging learners to take an active role in their learning process, this integrated approach can significantly contribute to the regulation of their learning activities and ultimately lead to improved academic achievement. Therefore, this study focused on investigating the use of SRL to improve learners’ speaking and listening skills and on delving into the learning situation which affects the speaking and listening skills viewed from self-confidence and linguistic awareness. The study was conducted in qualitative ways. The research instruments employed observation sheets and interview guidelines. The data are analyzed in qualitative ways, i.e., data condensation, data display, and drawing conclusions and verification. The findings showed that the implementation of self-regulated learning strategies in the teaching of speaking and listening skills can significantly impact learners' language development. Self-confidence and linguistic awareness act as catalysts for improving learners' speaking and listening proficiency. By setting goals, monitoring progress, and engaging in self-reflection, learners can boost their self-confidence, leading to more effective communication. Additionally, heightened linguistic awareness enables learners to refine their language skills, enhancing both speaking fluency and listening comprehension. The findings hold the potential to inform educational practitioners, policymakers, and researchers about the value of incorporating SRL methods effectively into language teaching, leading to more effective and tailored pedagogical approaches.